2007
DOI: 10.1038/sj.emboj.7601517
|View full text |Cite
|
Sign up to set email alerts
|

Suv39H1 and HP1γ are responsible for chromatin-mediated HIV-1 transcriptional silencing and post-integration latency

Abstract: HIV‐1 gene expression is the major determinant regulating the rate of virus replication and, consequently, AIDS progression. Following primary infection, most infected cells produce virus. However, a small population becomes latently infected and constitutes the viral reservoir. This stable viral reservoir seriously challenges the hope of complete viral eradication. Viewed in this context, it is critical to define the molecular mechanisms involved in the establishment of transcriptional latency and the reactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
203
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 282 publications
(213 citation statements)
references
References 65 publications
10
203
0
Order By: Relevance
“…Proviral silencing also involves dimethylation of H3K9 through KMTase G9a (61). In addition, du Chene et al reported that enrichment of H3K9me3 and transcriptional repression of integrated HIV-1 LTRs involve recruitment of the KMTase SUV39H1 (63). It remains to be established whether these factors are also involved in the expression of HERV-W during virus infection.…”
Section: Discussionmentioning
confidence: 99%
“…Proviral silencing also involves dimethylation of H3K9 through KMTase G9a (61). In addition, du Chene et al reported that enrichment of H3K9me3 and transcriptional repression of integrated HIV-1 LTRs involve recruitment of the KMTase SUV39H1 (63). It remains to be established whether these factors are also involved in the expression of HERV-W during virus infection.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with H3K27me3 being generally a more flexible epigenetic repressive mark and with the likelihood that most of the inducible latent provirus is silenced through pathways involving H3K27me3, rather than H3K9me3. H3K9me3 has only been found in a few HIV-1 latency studies and re-activation of latent provirus carrying this mark has either not been observed after strong stimulation (with Phorbol-Myristate-Acetate treatment) or has required silencing of HP1-γ or other factors through RNAi [178,179] . This supports H3K9me3 as a more robust repressive epigenetic mark.…”
Section: Hiv Latencymentioning
confidence: 99%
“…For this purpose, we used the 2E11 (also called pU2OS_Exo1) cell line, that harbors an integrated inducible HIV-1 reporter gene containing a splice site for SF2/ASF. An additional RNA tag (MS2) was inserted to facilitate its visualization by in situ hybridization (Boireau et al, 2007;du Chéné et al, 2007). The ability of SF2/ASF to be recruited to nascent pre-mRNAs was estimated by measuring the relative level of the protein at the transcription site (TS, visualized as a nuclear dot by in situ hybridization with a MS2-Cy3 probe) compared with its level at a neighboring NS ( Figure 11A and Figure S3).…”
Section: Roles Of 20s Proteasome-pa28␥ Complexes In the Structural Inmentioning
confidence: 99%
“…HeLa cells (ATCC, Manassas, VA), U 2 OS-tTA (Theis-Febvre et al, 2003), 2E11 cell line (Boireau et al, 2007;du Chéné et al, 2007), and MelJuso cell line expressing constitutively the LMP2-GFP fusion protein (Reits et al, 1997) were cultured as described in the respective articles. U 2 OS-tTA cells expressing stably ␣7-CFP or CFP were established as described (Theis-Febvre et al, 2003).…”
Section: Cell Culture and Transfectionmentioning
confidence: 99%